INTEGRATIVE MODEL FOR ADDRESSING EARLY MARRIAGE THROUGH A LEGAL ANTHROPOLOGY APPROACH IN BANYUWANGI REGENCY - Ayu Herlin Norma Yunita; Marwiyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to: 1) identify the factors triggering early marriage in Banyuwangi Regency; 2) examine public perceptions of early marriage; and 3) develop an integrative model to address early marriage through a Legal Anthropology approach. A qualitative research method with a critical analysis approach was employed, covering research location and timeframe, approach, data sources, data collection and validation techniques, and data analysis Finding indicate that Client-Centered Therapy (CCT) based on Legal Anthropology provides an effective alternative strategy to address persistent early marriage cases. This approach positions individuals as central agents in solution-finding while integrating cultural, customary, and legal contexts. Counselors facilitate adolescents, parents, and community leaders in expressing experiences, motivations, and social pressures underlying early marriage. The model harmonizes state law, customary law, and religious values, avoiding cultural conflicts. Its implementation has enhanced dialogue between youth and families, increased awareness of early marriage’s negative impacts, and established community-based prevention mechanisms. Thus, CCT grounded in Legal Anthropology not only empowers individual decision-making but also promotes social transformation toward child protection and gender equality.